Analysis of Moral Hazard during Financial Crisis and Present Time - Krejčí, Martin (2018)
The aim of this thesis is to comprehensively describe the financial crisis 2007-2008, identify moral hazard manifestations and analyze the changes since the crisis with the attempt to evaluate how have the moral hazard problems evolved over time. The work begins with a detailed description of moral hazard and the financial crisis. Three key areas of moral hazard during the crisis are identified – regulation, corporate level strategy and remuneration. These areas are then qualitatively analyzed in present time through in-depth expert interviews supported by secondary research. The research shows that while some of the changes since the crisis were positive, from the moral hazard perspective they have been rather unsuccessful and even created new sources of moral hazard. The thesis concludes with a future outlook at possible threats to global economy. As part of this outlook, the author forms a hypothesis about a new moral hazard risk in the housing market.